Characterization data of reference materials used for phase II of the priority program DFG SPP 2005 “Opus Fluidum Futurum – Rheology of reactive, multiscale, multiphase construction materials” - U. Pott; C. Crasselt; N. Fobbe; M. Haist; M. Heinemann; S. Hellmann; D. Ivanov; C. Jakob; D. Jansen; L. Lei; R. Li; J. Link; et al. (Data in Brief, 2023)
A thorough characterization of base materials is the prerequisite for further research. In this paper, the characterization data of the reference materials (CEM I 42.5 R, limestone powder, calcined clay and a mixture of these three components) used in the second funding phase of the priority program 2005 of the German Research Foundation (DFG SPP 2005) are presented under the aspects of chemical and mineralogical composition as well as physical and chemical properties. The data were collected based on tests performed by up to eleven research groups involved in this cooperative program.